Keterampilan Menulis Teks Deskripsi Menggunakan Aksara Lontarak dengan Teknik Pengamatan Objek pada Siswa Kelas VIII SMP Negeri 5 Barru - Ananda, Nabila Tri; Syamsudduha, Syamsudduha; Asri, Aswati (Nuances of Indonesian Language, 2024)
Description Text Writing Skills Using Lontara Script with Object Observation Techniques in Class VIII Students of SMP Negeri 5 Barru". Thesis, Regional Language and Literature Education Study Program, Department of Indonesian Language and Literature, Faculty of Language and Literature, Makassar State University, (supervised by Syamsudduha, and Aswati Asri). This research aims to describe the skills of writing descriptive text using the Lontara script with object observation techniques for class VIII students at SMP Negeri 5 Barru. This research is quantitative descriptive. The population in this study was all 196 class VIII students. The sample determined was 32 people. The data analysis technique used to collect data in this research is the written test technique. The results of this research show that the skills in writing descriptive text using the Lontara script with object observation techniques in class VIII students at SMP Negeri 5 Barru are in the unskilled category. This was shown from the 32 samples that had been determined, 6 students (19%) got a score of 75-100, and 26 students (81%) got a score of 0-74.